3D printing to enable the reuse of marine plastic waste with reduced environmental impacts. (28th July 2022) - Cañado, Naiara; Lizundia, Erlantz; Akizu‐Gardoki, Ortzi; Minguez, Rikardo; Lekube, Blanca; Arrillaga, Alex; Iturrondobeitia, Maider
Abstract: Over the years, our oceans have witnessed an enormous accumulation of marine plastic waste resulting from ocean‐related economic activities. As plastic pollution adversely affects marine wildlife and habitat, our society requires urgent solutions to address this increasingly alarming dilemma. Here, we turn our attention to circular economy principles to reduce the amount of nonbiodegradable petroleum‐based marine litter. We consider a production process based on 3D printing to fabricate products for the marine industry, which uses marine plastic waste as a source material. Additionally, the suitability of virgin bio‐based polyamide (bio‐PA), polylactic acid (PLA), and polyhydroxybutyrate (PHB) is explored. PHB is selected due to its extraordinary rapid biodegradation in aquatic environments. To quantify the environmental impacts of the proposed processes, a cradle‐to‐grave life cycle assessment (LCA) is applied according to ISO 14040:2006 and ISO 14044:2006 standards. Different end‐of‐life alternatives are proposed, including landfill deposition, thermal degradation, and composting. LCA results reveal that the use of marine plastic waste is environmentally preferred in comparison with bio‐PA, PLA, and PHB. Specifically, the global warming indicator, considered a prime driver toward sustainability, shows a 3.7‐fold decrease in comparison with bio‐PA. Importantly, the environmental impacts of PHB production through crude glycerol fermentation are quantified for the first time. Regarding the end‐of‐life options with a composting scenario, PLA and PHB are preferred as they yield biogenic carbon dioxide (CO2 ), which can be used as a renewable energy source.